1985
DOI: 10.1037/0022-0663.77.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Peer models: Influence on children's self-efficacy and achievement.

Abstract: Abstract:According to Bandura (1977Bandura ( , 1981Bandura ( , 1982, psychological procedures change behavior in part by creating and strengthening perceived self-efficacy, which refers to judgments of one's performance capabilities in a given domain of activity. Self-efficacy can influence choice of activities, effort expended, persistence, and task accomplishments. Efficacy information is conveyed through actual performances, vicarious (observational) experiences, forms of persuasion, and physiological index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
259
2
11

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(284 citation statements)
references
References 30 publications
12
259
2
11
Order By: Relevance
“…For example, Schunk and colleagues found that perceived self-efficacy for learning correlates positively with students' rate of solution of arithmetic problems (Schunk & Hanson, 1985;Schunk, Hanson, & Cox, 1987). Salomon (1984) has found that self-efficacy is positively related to self-rated mental effort and achievement during students' learning from text material that was perceived as difficult.…”
Section: Role Of Self-efficacy In Academic Motivationmentioning
confidence: 99%
“…For example, Schunk and colleagues found that perceived self-efficacy for learning correlates positively with students' rate of solution of arithmetic problems (Schunk & Hanson, 1985;Schunk, Hanson, & Cox, 1987). Salomon (1984) has found that self-efficacy is positively related to self-rated mental effort and achievement during students' learning from text material that was perceived as difficult.…”
Section: Role Of Self-efficacy In Academic Motivationmentioning
confidence: 99%
“…Interesting from the perspective of the goal of our study, is that modeling examples have not only been used for teaching problemsolving skills (e.g., Schunk, 1981;Schunk & Hanson, 1985;McLaren et al, 2008) but also for improving self-regulatory skills, for example in trying to improve dart-throwing skills (Kitsantas, Zimmerman, & Cleary, 2000) or writing skills (Zimmerman & Kitsantas, 2002). In the study by Kitsantas et al, for example, students were shown either coping models (models who initially made many mistakes but gradually eliminated them) or mastery models (models who showed flawless performance from the start).…”
Section: Methodsmentioning
confidence: 99%
“…Models of the same age and sex as children and whom children view as similar in competence may teach children skills and promote their self-efficacy for learning those skills. Schunk and Hanson (1985) found that children who observed a same-sex peer (student) model solve subtraction problems developed higher self-efficacy for learning to subtract than did children who observed a teacher model solve the same problems. …”
mentioning
confidence: 99%
“…The Schunk and Hanson (1985) subjects observed either a peer mastery or coping model solving subtraction problems that involved regrouping; type of modeled behavior did not, however, differentially affect children's self-efficacy, skillful performance, or perceptions of similarity in competence to the model. Although these subjects' prior successes in subtraction were limited to problems without regrouping, children may have drawn on these experiences and concluded that if the peer model could learn, they could as well.…”
mentioning
confidence: 99%